PERAN CAMAT DALAM PENGAWASAN PEMBANGUNAN INFRASTRUKTUR DESA DI KECAMATAN RANDANGAN KABUPATEN POHUWATO - Umar Sune; Rusni Djafar (JPPE : Jurnal Perencanaan & Pengembangan Ekonomi, 2025)
Village infrastructure development is one of the strategic instruments in accelerating regional development and improving community welfare. The success of village infrastructure development is not only determined by the availability of budget funds, but also by the effectiveness of supervision carried out by government officials, particularly the Sub-district Head (Camat) as a regional apparatus who has the authority to provide guidance and supervision over village governance. This study aims to identify and analyze the role of the Camat in supervising village infrastructure development in Randangan Sub-district, Pohuwato Regency. This research employs a qualitative approach with a descriptive method. The research informants consisted of nine individuals, namely the Camat of Randangan, the Sub-district Secretary, four Village Heads, and three community leaders. Data collection techniques included observation, in-depth interviews, and documentation. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing.The results of the study indicate that the role of the Camat in supervising village infrastructure development in Randangan Sub-district is manifested through direct and indirect supervision, preventive and repressive supervision, as well as internal and external supervision. The Camat actively conducts field visits, coordinates with village governments, and involves the community in the supervision process of development activities. Such supervision contributes positively to the quality of development outcomes, the timeliness of implementation, and increased community participation in village development.